Facile Synthesis of Palladium‐Based Nanocrystals with Different Crystal Phases and a Comparison of Their Catalytic Properties. Issue 49 (8th October 2021) - Janssen, Annemieke; Pawlik, Veronica; von Rueden, Alexander D.; Xu, Lang; Wang, Chenxiao; Mavrikakis, Manos; Xia, Younan
Abstract: A relatively unexplored aspect of noble‐metal nanomaterials is polymorphism, or their ability to crystallize in different crystal phases. Here, a method is reported for the facile synthesis of Ru@Pd core–shell nanocrystals featuring polymorphism, with the core made of hexagonally close‐packed ( hcp) ‐Ru while the Pd shell takes either an hcp or face‐centered cubic ( fcc) phase. The polymorphism shows a dependence on the shell thickness, with shells thinner than ≈1.4 nm taking the hcp phase whereas the thicker ones revert to fcc . The injection rate provides an experimental knob for controlling the phase, with one‐shot and drop‐wise injection of the Pd precursor corresponding to fcc ‐Pd and hcp ‐Pd shells, respectively. When these nanocrystals are tested as catalysts toward formic acid oxidation, the Ru@Pd hcp nanocrystals outperform Ru@Pd fcc in terms of both specific activity and peak potential. Density functional theory calculations are also performed to elucidate the origin of this performance enhancement. Abstract : There is a strong interest in developing phase‐controlled metal nanocrystals to enhance their catalytic activity. In this work, template‐directed growth is used to synthesize Ru@Pd nanocrystals with the Pd shells in either an fcc or hcp phase, and their catalytic properties are compared.